Heterogeneity in Economic Shocks and Household Spending in the US1. (March 2016) - Devlin‐Foltz, Sebastian; Sabelhaus, John
Abstract: Large swings in aggregate household sector spending, especially for big‐ticket items such as cars and housing, have been a dominant feature of the macroeconomic landscape in the past two decades. Income and wealth inequality increased over the same period, leading some to suggest the two phenomena are interconnected. Indeed, there is supporting evidence for the idea that heterogeneity in economic shocks and spending are connected, most notably in studies using local‐area geography as the unit of analysis. The Survey of Consumer Finances (SCF) provides a household‐level perspective on changes in wealth, income and spending across different types of families. The SCF confirms that inequality is indeed increasing in recent decades, and the data provide support for the proposition that shocks to income and wealth are indeed related to large swings in spending across and within birth cohorts. However, the economic shocks associated with the Great Recession and changes in spending and debt to income ratios are widespread, and inconsistent with a narrow focus on the experiences and changes in behaviour of particular (especially low‐ and modest‐income) households.